Crohn's Disease and Asperger Syndrome: Not Just a Coincidence?. Issue 6 (June 2016) - Fragaki, Maria; Karmiris, Konstantinos; Paspatis, Gregorios A.
Abstract : Article first published online 22 April 2016.